2011
DOI: 10.3109/08958378.2011.592869
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous silica coatings on magnetic nanoparticles enhance stability and reduce toxicity toin vitroBEAS-2B cells

Abstract: MNPs coated with amorphous silica are protected from acidic erosion. Correspondingly, the particle stability translates into reduced cytotoxicity and cellular influence on human airway epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…In accordance with data reported in the literature (Baber et al, 2011), we confirmed that silica coating prevents the cytotoxicity of SPIONs as measured by the MTT assay. In our study, exposure to uncoated-SPIONs did not increase the quantity of acid organelles, while their cytotoxic action was detected at concentrations above 20 lg/mL.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In accordance with data reported in the literature (Baber et al, 2011), we confirmed that silica coating prevents the cytotoxicity of SPIONs as measured by the MTT assay. In our study, exposure to uncoated-SPIONs did not increase the quantity of acid organelles, while their cytotoxic action was detected at concentrations above 20 lg/mL.…”
Section: Discussionsupporting
confidence: 80%
“…High intracellular iron ion concentrations potentially lead to oxidative stress generated cytotoxicity (Sarkar et al, 2014). It is suggested that silica coating serves as a protective barrier that prevents iron ion dissolution from the SPIONs and thus lowers the cytotoxicity of SiO 2 -SPIONs (Baber et al, 2011). One possible explanation for different cellular effects of uncoated-and SiO 2 -SPIONs could be the fact that uncoatedSPIONs are internalized and degraded in lysosomes, which releases the toxic amount of iron ions, while the internalization of persistent SiO 2 -SPIONs did not lead to the release of a toxic amount of ions, but instead resulted in the intracellular accumulation of SiO 2 -SPIONs in acid organelles, which is a known outcome when cells endocytose hardly degradable material (Pentchev et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic NPs could be protected from acidic erosion when coated with amorphous silica, stabilizing the NPs and reducing toxicities in in vitro cellular toxicity assays [62]. According to the charges of side chains, the same NPs exerted different toxicities in various cell types [60].…”
Section: Nanotechnology and Nanotoxicology In Retinopathy: Friendsmentioning
confidence: 99%
“…An amorphous silica coating of magnetic iron oxide nanoparticles was found to reduce cytotoxicity to human airway epithelial cells [162]. Whether these coatings of carbon nanotubes and iron oxide nanoparticles reduce hazards to human health in practice has so far not been determined.…”
Section: Hazard and Risk Reductionmentioning
confidence: 99%